Comparison between ultrafine and fine particulate matter collected in Lebanon: Chemical characterization, in vitro cytotoxic effects and metabolizing enzymes gene expression in human bronchial epithelial cells. (October 2015) - Borgie, Mireille; Dagher, Zeina; Ledoux, Frédéric; Verdin, Anthony; Cazier, Fabrice; Martin, Perrine; Hachimi, Adam; Shirali, Pirouz; Greige-Gerges, Hélène; Courcot, Dominique
Abstract: During the last few years, the induction of toxicological mechanisms by atmospheric ultrafine particles (UFP) has become one of the most studied topics in toxicology and a subject of huge debates. Fine particles (FP) and UFP collected at urban and rural sites in Lebanon were studied for their chemical composition and toxicological effects. UFP were found more enriched in trace elements, secondary inorganic ions, total carbon and organic compounds than FP. For toxicological analysis, BEAS-2B cells were exposed for 24, 48 and 72 h to increasing concentrations of FP, water-UFP suspension (UFPw ) and UFP organic extract (UFPorg ). Our findings showed that UFP caused earlier alterations of mitochondrial metabolism and membrane integrity from the lowest concentrations. Moreover, a significant induction of CYP1A1, CYP1B1 and AhRR genes expression was showed after cells exposure to UFPorg and to a lesser extent to UFPw and FP samples. Highlights: The main source of air pollution in Beirut is road traffic and generator sets. More trace elements, secondary inorganic ions and organic compounds are found in UFP. UFP cause early alterations of mitochondrial metabolism and membrane integrity. PM induce XME gene expression leading to the formation of PAHs-reactive metabolites. All the results evidenced a higher toxicity of UFP compared to FP. Abstract : Ultrafine particles collected in Lebanon: higher organic compounds contents than in fine particles and therefore higher induction of xenobiotic-metabolizing enzymes genes expression leading to more DNA damages.